THE REFLECTION OF THE SOCIAL ENVIRONMENT IN THE FORMATION OF THE ADOLESCENT PSYCHE IN THE WORKS OF KHUDOYBERDI TOKHTABOYEV AND CHRISTOPHER PAUL CURTIS - Kodirjonova Ikbola Bahodir kizi (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, it is revealed with examples how the complex social environment is reflected in children's psyche and how negatively it affects children in American and Uzbek children's literature. Through the analysis, it can be observed that there are some similarities and differences in style and in the depiction of the spirituality and social situation in American and Uzbek children's literature.